ASSESSMENT OF CITIZENS'AWARENESS REGARDING ORAL HYGIENE AND PREVENTION OF DENTAL DISEASES - L.F. Kaskova; O.S. Pavlenkova; M.O. Sadovski; L.I. Amosova (Український стоматологічний альманах)
Recently, sanitary and educational work for the prevention of dental diseases in children is widely implemented, but the problem of awareness and oral hygiene in young and middle-aged people remains quite relevant.